The global status of research in prostate cancer bone metastasis: A bibliometric and visualized analysis - Lv, Zongwei; Wang, Xia; Zhu, Chunming; Wang, Kefeng (Frontiers in Medicine, 2022)
Backgroud: The aims of this paper are to understand the international frontier research direction and literature distribution through bibliometric analysis and visual analysis of prostate cancer (PCa) bone metastasis. Methods: The data were from the Web of Science core collection database, which collected 2,246 papers related to PCa bone metastasis from January 1, 2012 to December 31, 2021. The collected data were analyzed using VOSviewer software for citation, co-authorship, co-citation, bibliometric coupling, and co-occurrence. Results: The number of papers published each year has been rising over the past decade. The United States has published 890 papers, far more than any other countries. Through keyword co-occurrence analysis, the studies of PCa bone metastasis can be divided into four categories: "basic research", "auxiliary diagnosis and treatment", "clinical trial", and "prognosis". In recent years, the focus of research has gradually shifted from basic research to diagnosis and treatment of this disease. With the gradual maturity of imaging techniques such as PSMA PET/CT and the development of radium-223 and androgen receptor antagonists, a window has been opened for patients with PCa bone metastasis. Conclusions: Our results provide a comprehensive overview of the research priorities and future directions of PCa bone metastasis, which can further accurately guide investigators on diagnosis, treatment, and personalized prevention.